The Review Of Academic Perception, Level Of Metacognitive Awareness And Reflective Thinking Skills Of Science And Mathematic University Students - Ayazgok, Busra; Aslan, Hatice (Elsevier Science Bv, 2014)
The aim of this study is to determine science and mathematics university students's academic perception, level of metacognitive awareness and reflective consideration skills and to ascertain connection between them according to age, sexuality, level of class. The sample of the study consists of university students' choosen by random. To analyse the data we handle technique of statistics such that mean, standard deviation, t test, analysis of variance (ANOVA) and multiple linear regression. The results will be interpretended according to science and mathematics students and then provided suggestions for students. (C) 2014 The Authors. Published by Elsevier Ltd.
4th World Conference on Learning, Teaching and Educational Leadership (WCLTA) -- OCT 27-29, 2013 -- Univ Barcelona, Barcelona, SPAIN
Keywords: Science education; mathematics education; metacognitive awareness; reflective thinking